2023
DOI: 10.1186/s12860-023-00477-2
|View full text |Cite
|
Sign up to set email alerts
|

SCAT8/miR-125b-5p axis triggers malignant progression of nasopharyngeal carcinoma through SCARB1

Abstract: Nasopharyngeal carcinoma is a tumor with high malignancy and poor prognosis, which severely affects the health of the patients. LncRNAs and microRNAs are crucial for the occurrence and development of nasopharyngeal carcinoma, which regulate the progression of nasopharyngeal carcinoma through the ceRNA network. SCARB1 plays an essential role in nasopharyngeal carcinoma. However, the mechanism underlying the regulation of SCARB1 in nasopharyngeal carcinoma through non-coding RNAs remains unclear. Our findings in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…SCAT8 may be a new gene needed to be further studied because rare studies reported its functions except of one about gastric cancer 63 and one focusing on nasopharyngeal carcinoma. 64 There had been studies linking lncRNA LUCAT1 with inflammatory diseases: Zhao et al found LUCAT1 was upregulated in the serums of chronic obstructive pulmonary disease patients. LUCAT1 expression was positively correlated with the levels of pro-inflammatory cytokines IL1β, IL6 and TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…SCAT8 may be a new gene needed to be further studied because rare studies reported its functions except of one about gastric cancer 63 and one focusing on nasopharyngeal carcinoma. 64 There had been studies linking lncRNA LUCAT1 with inflammatory diseases: Zhao et al found LUCAT1 was upregulated in the serums of chronic obstructive pulmonary disease patients. LUCAT1 expression was positively correlated with the levels of pro-inflammatory cytokines IL1β, IL6 and TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison between NC and B320 groups revealed an upregulation of SCARB1. Through analysis, a regulatory network was discovered that involved SCAT8/miR-125b-5p axis and contributed to the malignant progression of nasopharyngeal carcinoma by inducing SCARB1 expression [ 70 ]. Furthermore, SCARB1 was found to be linked to an increase in high-density lipoprotein-cholesterol and a heightened risk of myocardial infarction [ 71 ].…”
Section: Discussionmentioning
confidence: 99%